SYUKURAN HASIL BUMI (SABUMI) DI DESA GARATENGAH KECAMATAN JAPARA KABUPATEN KUNINGAN BERSAMA MAHASISWA KKN MBKM UNIVERSITAS MUHAMMADIYAH KUNINGAN - Firmansyah, Muhammad Teguh; Sya’bani, Wildan Nur; Nurhidayatillah, Anisa; Nurjanah, Hifni Fitrih (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This community service is entitled Syukuran Hasil Bumi (Sabumi) in Garatengah Village, Japara District, Kuningan Regency with KKN MBKM Students of Muhammadiyah Kuningan University. This research method was conducted using a quantitative approach supported by quantitative data. The quantitative method was carried out using a survey method on respondents, namely the Garatengah village community and village officials. The results of the PkM show that the various potentials that Garatengah Village has, KKN MBKM students from Muhammadiyah Kuningan University of Garatengah Village group then contribute to sabumi (village birthday) activities. One of them is the village harvest thanksgiving event once a year. This activity is designed to preserve the garatengah urban forest and honor the ancestors of garatengah village. Where the sabumi event contains goat slaughtering, surrounding the urban forest and singing and walking while carrying the tread of the village of Garatengah. This activity is held once a year on Friday keliwon.